2021
DOI: 10.1001/jamanetworkopen.2021.7557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Technology-Assisted Integrated Diabetes Care Program on Cardiometabolic Risk Factors Among Patients With Type 2 Diabetes in the Asia-Pacific Region

Abstract: IMPORTANCEMany health care systems lack the efficiency, preparedness, or resources needed to address the increasing number of patients with type 2 diabetes, especially in low-and middle-income countries. OBJECTIVE To examine the effects of a quality improvement intervention comprising information and communications technology and contact with nonphysician personnel on the care and cardiometabolic risk factors of patients with type 2 diabetes in 8 Asia-Pacific countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The built-in protocols provide guidance to nurses for systematic data collection and for generating a simple-to-read personalized report that includes risk categories, trends for modifiable risk factors (BP, lipids, HbA 1c , and body weight), future risks for major events, and tailored decision support. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The built-in protocols provide guidance to nurses for systematic data collection and for generating a simple-to-read personalized report that includes risk categories, trends for modifiable risk factors (BP, lipids, HbA 1c , and body weight), future risks for major events, and tailored decision support. 31 …”
Section: Discussionmentioning
confidence: 99%
“…In a previous JADE RCT of 20 834 patients with type 2 diabetes in 8 countries or regions, the JADE technology–assisted intervention group was more likely to attain at least 2 treatment targets (HbA 1c level <7.0% [53 mmol/mol], BP <130/80 mm Hg, or LDL-cholesterol level <2.6 mmol/L) after 12 months, with larger effects (odds ratios) in low- and middle-income countries compared with high-income countries (50% vs 20%). 31 …”
Section: Discussionmentioning
confidence: 99%
“…For the DKD patients in the ERSD, renal replacement therapy is an effective means to prolong the survival time, for which MHD is considered the primary renal replacement therapy method. Clinical research suggested that favorable hemodialysis requires patients to precisely control their fluid intake and diet, which greatly changes the patients' previous living habits [7][8][9][10][11][12][13][14][15][16][17][18]. Most patients refuse to receive the long-term hemodialysis treatment psychologically and therefore they tend to generate some negative moods (including depression and anxiety) [19].…”
Section: Discussionmentioning
confidence: 99%
“…The negative associations between healthy lifestyle and age at diagnosis might be confounded by behavioral changes after diagnosis although results were consistent in newly diagnosed patients. The JADE Register uses a pragmatic design to implement data-driven integrated care in a real-world setting [ 38 , 39 ]. Thus, instead of using complex instruments, we used simple questionnaires based on available evidence to assess behavioral factors.…”
Section: Discussionmentioning
confidence: 99%